Efecto de la aplicación de nuevas tecnologías en el tratamiento de las aguas de bombeo, sobre la calidad de los efluentes de la Empresa Pesquera Pelayo S.A.C. de harina y aceite de pescado de puerto Supe - Quevedo Gonzáles, Henry Norberto (2016)
The effect of the application of new technologies is determined, in the effluent treatment fishery from Pesquera Pelayo SAC company, which produces fish meal and fish oil, in order to reduce the load of pollutants into the marine receiving body; Puerto Supe bay; and comply with national environmental regulations. The research was conducted by comparing the analysis of effluent discharges, such as TSS (total suspended solids), oil and grease, BOD5 (biological oxygen demand), pH (hydrogen ion concentration) before and after the application of new technologies for the treatment of these effluents, specifically with the application of chemical products for the coagulation and flocculation of suspended solids. With the results, it was concluded that, with the application of chemical processes, after water treatment pumping, has been greatly reduced pollutant loading of treated effluent, as regards the variables oils and fats, TSS (total suspended solids), and has maintained the values of pH (hydrogen ion concentration) within the range of the LMP (maximum permissible limits) established in the Supreme Decree No. 010 - 2008 - PRODUCE.